Presentation of the final document of the employment table - Castellanos, Martín (1999)
This presentation is the product of the work of three meetings that have meant a process of progressive incorporation of different institutions, which to date add up to 48, between social organizations, private and state institutions and also companies. The issue has been discussed with all of them. The constitution of the employment table is based on the challenge of making the values ​​of the kingdom of God more present in the world of work, taking into account the value and importance of work as a central element in people's lives, in a that allows to live with dignity.